BASELINE SATTLER LAYER–CHORIOCAPILLARIS COMPLEX THICKNESS CUTOFFS ASSOCIATED WITH AGE-RELATED MACULAR DEGENERATION PROGRESSION. Issue 9 (September 2022) - Amato, Alessia; Arrigo, Alessandro; Borghesan, Federico; Aragona, Emanuela; Vigano', Chiara; Saladino, Andrea; Bandello, Francesco; Battaglia Parodi, Maurizio
Abstract : This study assesses the influence of choroid overall and sublayer thickness in the progression of age-related macular degeneration and suggests that a thinner baseline Sattler layer–choriocapillaris complex is associated with a worse disease course. Abstract : Purpose: To assess the relationship between choroidal overall and sublayer thickness and age-related macular degeneration (AMD) stage progression. Methods: A prospective, observational case series was performed. Two hundred and sixty-two eyes of 262 patients with different stages of AMD were imaged by optical coherence tomography. Age-related macular degeneration stage, choroidal thickness, Sattler layer–choriocapillaris complex thickness (SLCCT), and Haller layer thickness were determined at the baseline visit, at a 1-year follow-up visit, at a 2-year follow up visit, and at a final visit (performed after a mean of 5 ± 1 year from the baseline visit). Results: Baseline AMD stages were distributed as follows: early AMD (30 eyes; 12%), intermediate AMD (97 eyes; 39%), and late AMD (126 eyes; 49%). At the final follow-up, AMD stages were so distributed: early AMD (14 eyes; 6%), intermediate AMD (83 eyes; 33%), and late AMD (156 eyes; 61%). Each group showed a statistically significant decrease in choroidal thickness values over the entire follow-up ( P < 0.001), and SLCCT reduction was associated with AMD progression ( P < 0.001). Moreover, SLCCT quantitative cutoffs of <20.50 µ m and <10.5 µ m were associated with a moderate and high probability of AMD progression, respectively, and SLCCT quantitative cutoffs of <18.50 µ m and <8.50 µ m implied a moderate and high probability of macular neovascularization onset, respectively. Conclusion: Progressive choroidal impairment contributes to AMD progression. Among choroidal layers, a reduced SLCCT is a promising biomarker of disease worsening, and its quantitative evaluation could help to identify patients at higher risk of stage advancement.